Cultural Tourist Attractions at The Cap Go Meh Festival in Singkawang City - Rhea Mandasari; Budi Setiawan (Jurnal Syntax Transformation, 2023)
Cultural tourism is one of the supporting or driving factors for the Indonesian tourism sector which plays quite an important role. Culture can be an attraction that can attract domestic and foreign tourists to learn about a culture in a particular area, one of which is the Cap Go Meh Festival in Singkawang City. The Cap Go Meh Festival has now become an annual event that has been seen by the eyes of the world since 2008 and was recognized as a National Intangible Cultural Heritage (WBTB) 2020 and then named as one of the best events in Indonesia's Top 10 in 2023. Through the Cap Go Meh Festival as a cultural attraction , apart from being an entertainment event, it is also a cultural communication tool that represents traditions, history, culture, and introduces the regional culture of a place. The research was conducted to determine the attractiveness of the Cap Go Meh Festival cultural tourism which will be held in 2023 using the qualitative descriptive method. The research subjects used key informants, namely the Deputy Chief Executive, Dayak Traditional Institution, and Participants of the 2023 Cap Go Meh Festival. The research results showed that the Cap Go Meh Festival met the criteria as an attraction that had aspects of uniqueness, beauty and value contained in it.